Environmental Pollution and Health Problems of Workers in Tobacco Industries - Elias, MS; Saha, NK (Journal of Life and Earth Science, 2011)
The effect of environmental pollution on subjective and mental health of the workers in tobacco industries has been investigated. A total of 540 workers, 340 from tobacco (polluted) industries and the remaining 200 from non-tobacco industries, were selected using simple random sampling technique. Workers included in the sample were interviewed with three measuring instruments: (a) The Inventory of Subjective Health, (b) The General Health Questionnaire and (c) The Interview Schedule on Personal and Health Related Questionnaire. The results showed that the workers of tobacco industries suffered more from subjective health and mental health related problems than those of the non-tobacco industries. The older (≥20 yrs) workers perceived relatively better subjective health than the younger (<20 yrs) whereas latter perceived better mental health than the former. Male workers were found to have better subjective and mental health compared to the female workers, and the unmarried workers had better mental health than the married workers. Moreover, unhygienic home environment, malnutrition, lack of health care facilities, use of raw materials, anxiety, tension and job dissatisfaction were some of the health risk factors as perceived by majority respondents of tobacco industries than that of the non-tobacco industries. Key words: Pollution; subjective health; mental health; tobacco industry DOI: 10.3329/jles.v3i0.7439 J. Life Earth Sci., Vols. 3-4: 13-17, 2009